2005
DOI: 10.1124/mol.104.008268
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Mutation Encoding a C Terminus-Truncated 5-Hydroxytryptamine2B Receptor Is a Gain of Proliferative Functions

Abstract: Although potentially implicated in several physiological functions, few functional mutations have been identified in the human 5-hydroxytryptamine (HT) 2B receptor gene. A heterozygous mutation R393X in the 5-HT 2B receptor was recently identified in a patient diagnosed with pulmonary hypertension after intake of the anorexigenic dexfenfluramine. Although reported to generate a lack of function, this C terminus-truncated 5-HT 2B receptor should somehow affect transduction pathways relevant to pulmonary hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…At higher doses, 5-HT had no effect on ICC numbers. This lack of effect at higher concentrations may be due to receptor internalization 59 or desensitization 60 or is possibly due to an effect of 5-HT on other receptors.…”
Section: Discussionmentioning
confidence: 97%
“…At higher doses, 5-HT had no effect on ICC numbers. This lack of effect at higher concentrations may be due to receptor internalization 59 or desensitization 60 or is possibly due to an effect of 5-HT on other receptors.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the coexpression of 5-HT 1B and 5-HT 2B receptors in various tissues including endothelial and smooth muscle cells (Ullmer et al, 1995), and given the inhibitory effect of 5-HT 2B receptors on 5-HT 1B receptor signaling (Tournois et al, 1998), physical interaction between the two receptors seems plausible. The internalization of the 5-HT 2B receptor is faster than that of 5-HT 2A and 5-HT 2C receptors (Porter et al, 2001;Schaerlinger et al, 2003;Deraet et al, 2005), although the mechanism underlying this distinction has not been uncovered. In this work, we investigated potential 5-HT 1B/2B receptor interactions by examining the colocalization and internalization kinetics of 5-HT 1B and 5-HT 2B receptors expressed alone or together.…”
mentioning
confidence: 99%
“…First, a mutation causing premature truncation of 5-HTR 2B was described in a patient with PAH associated with fenfluramine use [46]. Although originally considered a lossof-function mutation, subsequent analysis indicated that this mutation was associated with a complete loss of inositol 1,4,5-trisphosphate and a partial loss of nitric oxide synthase stimulation, with a strong gain of efficacy in cell proliferation [47]. Secondly, acute administration of PRX-08066 resulted in a reduction in systolic pulmonary blood pressure during exercise-induced hypoxia in humans without effect on systemic blood pressure [48].…”
Section: Discussionmentioning
confidence: 99%